Novel Aspects of Cardiac Ischemia and Reperfusion Injury Mechanisms - T. A. Yagudin; A. t Shabanova; Hong-Yu Liu (Креативная хирургия и онкология, 2019)
Introduction. The present article, in which a contemporary analysis of the literature on the pathophysiology of ischemic and reperfusion injury (IRI) of the myocardium is presented, focuses on the possible role played by of the calpain system and oxidative stress. Several process development options were proposed, including cytosolic and mitochondrial Ca2+ overload, reactive oxygen stress release, acute inflammatory response and metabolic degradation. The combined effect of all of the above factors produces irreversible ischemic and reperfused damage of cardiomyocytes.Materials and methods. The role of the calpain system in the creation of myocardial IRI was experimentally investigated. It was found that active calpain substrates play a significant role in the processes of cell cycle, apoptosis and differentiation, adversely affecting cardiomyocyte functionality. The calpain system is part of an integrated proteolytic system that is critical to the relationship between the structure and function of the cardiac sarcomere. Uncontrolled activation of calpain is indicated in the pathophysiology of many cardiovascular disorders. As shown by research, inhibitor calpain reduces the size of the zone of infarction following ischemia reperfusion and thus lessens the risk of “stunning” the myocardium. As is known, a consequence of IRI is acute myocardial infarction (AMI), which is a central factor in cardiovascular disease (CVD) and is one of the primary causes of mortality. Understanding the exact pathophysiological mechanisms remains an urgent problem for clinical physicians. To date, the mechanisms of IRI are not fully known, which creates certain difficulties in further treatment and prevention tactics. In addition, myocardial IRI is also an important issue for pathoanatomical service, since sudden coronary death can occur despite timely reperfusion therapy following AMI.Conclusion. The development of strategies for creating conditions that limit the degree of damage to myocardial tissues significantly increases the ability of the heart to withstand ischemic damage.